(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
This research aim to analyze and control the sources and impact of pollution on the Jhelum River in India. The pollution of water bodies due to discharge of untreated or inadequately treated wastewater has become a major environmental concern worldwide. Effluent Treatment Plants (ETPs) are an effective tool for controlling water pollution and can significantly improve the water quality of rivers and other water bodies. This research aims to study the effectiveness of ETPs in controlling water pollution by analyzing the design, operation, and performance of ETPs in various industries and communities. The study involves a comprehensive review of literature on ETPs, including their design, operation, and performance. The study also involves a case study of the Jhelum river in India, which has been heavily polluted due to discharge of untreated wastewater from various sources. The case study analyzes the design and operation of the ETPs installed in the industries located in India which can be used in Kashmir region for controlling the pollution of Jhelum River and evaluates their effectiveness in controlling water pollution. The study finds that ETPs are an effective tool for controlling water pollution and can significantly improve the water quality of rivers and other water bodies. The study also finds that the design and operation of ETPs are critical factors that determine their effectiveness in controlling water pollution. The study ETP also highlights the importance of proper monitoring, maintenance, and operation of ETPs, as well as appropriate discharge standards and regulations to ensure that the effluent does not harm the river ecosystem or human health. Overall, this research provides a comprehensive analysis of the effectiveness of ETPs in controlling water pollution and highlights the importance of proper design, operation, and regulation of ETPs for effective pollution control. The findings of this study can help guide policymakers and industry leaders in developing and implementing effective pollution control strategies to improve water quality and protect the environment and public health.